The striker [large type] : an Isaac Bell adventure - Cussler, Clive (Cussler, Clive. Isaac Bell novels., 2013)
After witnessing a terrible coal mining accident, Detective Isaac Bell hunts for the high-level saboteurs he believes are responsible.